“School Strike 4 Climate”: Social Media and the International Youth Protest on Climate Change - Boulianne, Shelley (2020)
Beginning in 2018, youth across the globe participated in protest activities aimed at encouraging government action on climate change. This activism was initiated and led by Swedish teenager, Greta Thunberg. Like other contemporary movements, the School Strike 4 Climate used social media. For this article, we use Twitter trace data to examine the global dynamics of the student strike on March 15, 2019. We offer a nuanced analysis of 993 tweets, employing a combination of qualitative and quantitative analysis. Like other movements, the primary function of these tweets was to share information, but we highlight a unique type of information shared in these tweets—documentation of local events across the globe. We also examine opinions shared about youth, the tactic (protest/strike), and climate change, as well as the assignment of blame on government and other institutions for their inaction and compliance in the climate crisis. This global climate strike reflects a trend in international protest events, which are connected through social media and other digital media tools. More broadly, it allows us to rethink how social media platforms are transforming political engagement by offering actors—especially the younger generation—agency through the ability to voice their concerns to a global audience.